Computer simulation of the impact performance of a wire rope safety fence - Bateman, M.B; Howard, I.C; Johnson, A.R; Walton, J.M (International journal of impact engineering, 2001)
A computer simulation is developed which models the response mechanics of a roadway wire rope safety fence to a vehicular impact. The simulation is developed primarily as a design tool, the aim of which is to reduce the number of full-scale crash tests required during wire rope safety fence development. The experimental observations from full-scale impact tests undertaken at the Motor Industry Research Association are first presented. The simulation approach arising from these test observations is then described. The detailed theory, which models the dynamic motion of the vehicle and the quasi-static response of the fence, is then developed. A final discussion assesses those potential collapse mechanisms which are assumed to be insignificant and have consequently not been modelled. This discussion, which provides a preliminary validation of the basis of the simulation, indicates that the primary collapse mechanisms of the fence are modelled for a wide range of practical circumstances.